Fold-thrust belt geometry of the Eastern Ghats Mobile Belt, a structural study from its western margin, Orissa, India - BISWAL, TK (Journal of African Earth Sciences, 2000)
The deformation pattern of the western margin of the Eastern Ghats Mobile Belt reveals the overthrusting relationship of the mobile belt with the craton. The mobile belt is characterised by a nappe structure consisting of the Lathore Group and Turekela Group nappes, which display distinctive lithological assemblages and deformational structures. While the Lathore Group nappe is dominated by charnockitic gneisses and folded by east-west reclined folds, the Turekela Group is khondalitic and folded along a northeast-southwest axis. The study area, therefore, resembles a fold-thrust belt. However, in view of the post-kinematic nature of thrusting to folding, it is comparable with the Caledonides fold-thrust belt. (C) 2000 Elsevier Science Limited. All rights reserved.